The Impact of Accessibility and Nuisance on Neighbourhood Satisfaction near Sungai Buloh-Kajang (SBK) MRT Line - Mohd Faris, Dziauddin; Mohmadisa , Hashim; Zafirah , Al Sadat Zyed; Hanifah , Mahat (GEOGRAFI, 2024)
The presence of urban rail transit can impact residents both positively and negatively, especially those who live within walking distance to this infrastructure. Positive MRT externalities such as improved accessibility from home to work and other desirable destinations may be highly valued by residents, while negative externalities such as noise and visual obstruction can be perceived as highly undesirable and, in extreme cases, lead residents to move. Hence, this study aims to determine neighbourhood satisfaction among residents living near the SBK MRT Line. In this study, multivariate regression analysis was used as an analytical tool to model the satisfaction of residents living near the SBK MRT Line. The dependent variable is perceived neighbourhood satisfaction. Individuals were surveyed on five propositions related to neighbourhood and housing satisfaction. The results suggest that the perceived neighbourhood satisfaction of residents living near the SBK MRT line is mixed. As expected, the perceived effect of improved accessibility appears to have a statistically significant influence on neighbourhood satisfaction. Factors such as satisfaction with the short walk to the nearest MRT station and improved accessibility to work by MRT have a direct effect on neighbourhood satisfaction. In addition, seven factors or variables were used to estimate the impact of MRT line nuisance on neighbourhood satisfaction. The results suggest that two factors related to perceived noise play an important role in determining neighbourhood satisfaction. More specifically, the MRT noise that can be heard at home and concern about the health effects of noise are statistically significant; both negatively influence neighbourhood satisfaction. Interestingly, however, factors related to interest in the MRT or attitudes towards riding it to work and other destinations have no statistical effect on neighbourhood satisfaction, except a perceived positive relationship between the presence of an MRT line and higher property prices. In addition, two factors used to indicate environmental characteristics – satisfaction with crime levels and satisfaction with green space – appear to have a strong positive effect on neighbourhood satisfaction. Finally, two factors used to describe respondents’ demographic characteristics, married and homeowner, appear to be important factors explaining neighbourhood satisfaction. From a policy perspective, the findings from this study provide insights into the accessibility gains and other residential characteristics – such as neighbourhood aesthetics and location assets – that could compensate for or at least mitigate perceived nuisances related to MRT proximity. It also provides insights into groups of people and types of areas that may require a tailored approach or additional attention because of greater MRT nuisance perceptions.